2015
DOI: 10.1536/ihj.14-367
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Right Ventricle by Speckle Tracking and Conventional Echocardiography in Rats With Right Ventricular Heart Failure

Abstract: SummarySpeckle tracking echocardiography (STE) has been reported to be a promising technique for evaluating right ventricular (RV) function in the clinical setting. On the other hand, the usefulness of STE for RV evaluation in small animal models has not been clarified, although the rat model is among the most commonly used animal models to develop novel effective treatments against pulmonary hypertension and RV heart failure (HF).We validated the use of STE and conventional echocardiographic variables for eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
1
12
0
2
Order By: Relevance
“…RV myocardial performance index, which is also called Tei Index, has been proved to be more effective for analysis of global RV dysfunction than systolic and diastolic measures alone. 29) In our study, we found that RVF rats had prolonged MPI of right ventricles compared with normal controls. Besides, the geometry changes of RV also occurred, which was described by RV area and RVAW.…”
Section: Discussionsupporting
confidence: 50%
“…RV myocardial performance index, which is also called Tei Index, has been proved to be more effective for analysis of global RV dysfunction than systolic and diastolic measures alone. 29) In our study, we found that RVF rats had prolonged MPI of right ventricles compared with normal controls. Besides, the geometry changes of RV also occurred, which was described by RV area and RVAW.…”
Section: Discussionsupporting
confidence: 50%
“…In cor pulmonale , increased oxidative stress is correlated with a decrease in right ventricular function, which is considered to be the main determinant of functional capacity and survival of patients (van de Veerdonk et al ., ). In this study, RV dysfunction was confirmed using classical echocardiographic parameters of diastolic function (E/A ratio) and systolic function (FEC, FAC and TAPSE) (Rudski et al ., ; Kimura et al ., ). FAC expresses the percentage variation in the RV area between diastole and final systole, with values below 35% indicating systolic dysfunction (Rudski et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…[34][35][36] Among the several measurement parameters of RV function, TAPSE has been more extensively studied 34,35,37) because it is easily obtainable and reproducible. Previously, we reported that TAPSE < 15 mm was independently associated with adverse clinical outcomes after MC.…”
Section: Discussionmentioning
confidence: 99%